Beiträge zum Göttinger Umwelthistorischen Kolloquium 2007 2008 - Herrmann, Bernd (Universitätsverlag Göttingen, 2008)
This annual yearbook presents essays in environmental history based on lectures given at the Göttingen study group "Environmental History" by external authors. As previous yearbooks it is dedicated to the plurality of approaches in environmental history and serves as a valuable source for information about current research in that realm.